2003
DOI: 10.1002/nur.10074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress management on PNI‐based outcomes in persons with HIV disease

Abstract: A pretest-posttest, repeated-measures design was used to evaluate the effects of two stress management interventions on a battery of outcomes derived from a psychoneuroimmunological (PNI) framework. The effects of cognitive-behavioral relaxation training groups (CBSM) and social support groups (SSG) were compared with a WAIT-listed control group on the outcomes of psychosocial functioning, quality of life, neuroendocrine mediation, and somatic health. Participants were 148 individuals (119 men, 29 women), diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 59 publications
1
35
0
1
Order By: Relevance
“…The revised 40-item Coping subscale was modeled after the Revised Ways of Coping Checklist (Vitaliano, Maiuro, Russo, & Becker, 1985) and measures problem-focused, emotionfocused, and appraisal-focused coping strategies. Reliability (Stress subscale α = .83, Coping subscale α = .80 to .87) and validity of the DIS for the study population have consistently been supported (Cella, McCain, Peterman, Mo, & Wolen, 1996;McCain et al, 2003). For this sample, the means and standard deviations were as follows: Stress subscale 22.71 (14.37); Coping subscale: Problem-Focused 39.68 (7.50), Emotion-Focused 34.33 (6.59), Appraisal-Focused 47.47 (9.36).…”
Section: Dealing With Illness Scale (Dis; Mccain and Gramling 1992)mentioning
confidence: 77%
“…The revised 40-item Coping subscale was modeled after the Revised Ways of Coping Checklist (Vitaliano, Maiuro, Russo, & Becker, 1985) and measures problem-focused, emotionfocused, and appraisal-focused coping strategies. Reliability (Stress subscale α = .83, Coping subscale α = .80 to .87) and validity of the DIS for the study population have consistently been supported (Cella, McCain, Peterman, Mo, & Wolen, 1996;McCain et al, 2003). For this sample, the means and standard deviations were as follows: Stress subscale 22.71 (14.37); Coping subscale: Problem-Focused 39.68 (7.50), Emotion-Focused 34.33 (6.59), Appraisal-Focused 47.47 (9.36).…”
Section: Dealing With Illness Scale (Dis; Mccain and Gramling 1992)mentioning
confidence: 77%
“…The studies demonstrated varying degrees of positive change in levels of depression and anxiety, a decrease in fatigue, and an increased CD4 cell count, as well as changes in several key endocrine factors. Although sample sizes have been relatively small, results were promising but indicated a need for further research (Cruess et al, 2000;McCain, Munjas, Munro, Elswick, & Robins, 2003).Little research has focused on the impact that partners and the significant-other relationship have on the well-being of the PLWH; however, there are important rationale for incorporating partners in interventions designed to enhance quality of life and minimize secondary psychosocial morbidity. First, the infected individual is not the sole person to suffer the consequences of HIV; given systems theory, a burden on one person within a dyad affects the other individual as well (Minuchin & Minuchin, 1987).…”
mentioning
confidence: 99%
“…The studies demonstrated varying degrees of positive change in levels of depression and anxiety, a decrease in fatigue, and an increased CD4 cell count, as well as changes in several key endocrine factors. Although sample sizes have been relatively small, results were promising but indicated a need for further research (Cruess et al, 2000;McCain, Munjas, Munro, Elswick, & Robins, 2003).…”
mentioning
confidence: 99%
“…The meta-analysis conducted by Crepaz and colleagues 27 included 15 cognitive-behavioral randomized controlled trials (RCTs) designed to modify maladaptive cognitions, reduce negative affect, and improve immune functioning among PLWHA. 29,32,35,39,41,43,44,47,50,51,53,[56][57][58][59][60][61] Fourteen of these interventions included coping skills and stress management training; the remaining study focused exclusively on cognitive-behavioral therapeutic approaches to alleviate depressed mood and reduce anxiety, excluding modules on coping. This meta-analysis found that cognitive-behavioral interventions resulted in significant decreases in depression, anxiety, anger, and stress across studies (Table 1).…”
Section: Summary Of Previous Stress Management Reviewsmentioning
confidence: 99%